2021
DOI: 10.3390/diagnostics11040589
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Potential Serum Biomarker Panel for the Diagnosis and Prognosis of Cholangiocarcinoma Using Decision Tree Algorithms

Abstract: Potential biomarkers which include S100 calcium binding protein A9 (S100A9), mucin 5AC (MUC5AC), transforming growth factor β1 (TGF-β1), and angiopoietin-2 have previously been shown to be effective for cholangiocarcinoma (CCA) diagnosis. This study attempted to measure the sera levels of these biomarkers compared with carbohydrate antigen 19-9 (CA19-9). A total of 40 serum cases of CCA, gastrointestinal cancers (non-CCA), and healthy subjects were examined by using an enzyme-linked immunosorbent assay. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… 21 Other studies investigating the use of multiprotein signatures as novel biomarkers are limited by a small number of patients with BTC (n <70) and a lack of validation in independent cohorts. [38] , [39] , [40] , [41] , [42] …”
Section: Discussionmentioning
confidence: 99%
“… 21 Other studies investigating the use of multiprotein signatures as novel biomarkers are limited by a small number of patients with BTC (n <70) and a lack of validation in independent cohorts. [38] , [39] , [40] , [41] , [42] …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of MMP-7[ 57 ], DKK1[ 60 ], thrombospondin-2 (TSP-2)[ 61 ] and uPAR[ 59 ] assessed together with CA19-9 showed higher values of sensitivity and specificity than the markers measured individually to diagnose CCA patients. Not least, a biomarker panel consisting of five proteins investigated in a decision tree algorithms based study, namely S100A9, MUC5AC, TGF-β1, angiopoietin-2 (Ang-2), and CA19-9, showed to have the greatest diagnostic potential among all mentioned proteins towards CCA vs HC (sensitivity: 95%, specificity: 90%) and towards CCA vs non-CCA (sensitivity: 70%, specificity: 83%) differentiation[ 62 ].…”
Section: Proteinsmentioning
confidence: 99%
“…Subjected to meta-analysis, high levels of tissue PD-L1[ 17 ] and tissue protein S100P[ 69 ] were also proposed as potential prognostic markers of CCA. Out of a protein multimarker panel consisting of serum S100A9, MUC5AC, TGF-β1, Ang-2, and CA19-9, serum levels of TGF-β1 and Ang-2 provided predictive potential for both metastasis and TNM stage prognosis in CCA patients[ 62 ].…”
Section: Proteinsmentioning
confidence: 99%
“…This correlation is particularly strong in cases of HCC, especially its more aggressive forms [5,12]. Similarly, in CCA, ANG-2 has been identified as a significant biomarker that can aid in diagnosis and predict outcomes [13]. The vascular endothelial growth factor, commonly known as VEGF, is a protein that modifies the activity of ANG-2.…”
Section: Introductionmentioning
confidence: 99%